Stability Analysis Based on Caputo-Type Fractional-Order Quantum Neural Networks. (28th June 2021) - Dong, Yumin; Li, Xiang; Liao, Wei; Hou, Dong
Abstract : In this paper, a quantum neural network with multilayer activation function is proposed by using multilayer Sigmoid function superposition and learning algorithm to adjust quantum interval. On this basis, the quasiuniform stability of fractional quantum neural networks with mixed delays is studied. According to the order of two different cases, the conditions of quasi uniform stability of networks are given by using the techniques of linear matrix inequality analysis, and the sufficiency of the conditions is proved. Finally, the feasibility of the conclusion is verified by experiments.